Ninjin’yoeito suppressed the onset of arthritis, pain, and muscle atrophy in rheumatoid arthritis model mice - Suginohara, Takeshi; Kawaguchi, Megumi; Michihara, Seiwa; Fujita, Nina; Han, Li-Kun; Takahashi, Ryuji (Frontiers in Pharmacology, 2022)
Rheumatoid arthritis is one of the most common diseases in orthopedic surgery. The main symptoms are joint pain and systemic symptoms. In recent years, rheumatoid arthritis is known to cause sarcopenia. Ninjin’yoeito (NYT), a traditional Japanese medicine, has been prescribed for patients with post-illness or post-operative weakness, fatigue, loss of appetite, rash, cold limbs, and anemia. In addition to its traditional use, NYT has been prescribed for treating frailty in gastrointestinal, respiratory, and urinary functions. Further, NYT is known to be effective in suppressing muscle atrophy in the prior literature. The present study aimed to investigate whether NYT suppresses various symptoms of the Collagen-induced arthritis (CIA) model. Long-term administration of NYT inhibited the increases in arthritis scores, decreases pain threshold, and muscle atrophy in the CIA model. In addition, NYT inhibited the elevation of the plasma IL-6 level. These results suggest that NYT may have therapeutic effects on symptoms, muscle atrophy and increase in plasma IL-6 level caused by rheumatoid arthritis.